(untitled) (Bangladesh Journal of Microbiology, 2011)
The results revealed that 40% of fresh mushrooms, 93% of processed and preserved mushroom samples including mushroom-based food products were safe for human consumption from bacteriological point of view. The highest bacterial load recorded was 8.7 × 108 cfu / gm in the samples collected from Sutrapur area of Dhaka city. The results also indicated that 27, 13, 13 and 7% of the fresh mushrooms were contaminated with coliform, fecal coliform, E. coli and Salmonella sp. respectively. Thus those mushroom samples were not up to the mark for consumption, considering safety and sanitation point of view. In case of processed mushrooms and mushroom-based food products the results showed that 20% of dried mushrooms were contaminated with both coliform and fecal coliform, 7% of powdered mushrooms were contaminated with only coliform and 13% of mushroom soup powder were contaminated with coliform, E. coli and Salmonella sp. In case of preserved mushrooms, it was found that 7% of the canned mushrooms had count <10 cfu/gm which was unacceptable as per specifications for the canned food. However, the results also revealed that coliform, fecal coliform, E. coli and even Salmonella sp. were not detected in preserved mushrooms examined. DOI: http://dx.doi.org/10.3329/bjm.v27i2.9170 BJM 2010; 27(2): 42-45